Approach Methods of Processing by Non-pns Islamic Leader in Simokerto District Towards Religiosity in Elderly Congratulations at Assembly Taklim Al-Hidayah - Zarnuji, Aqib (Journal International Dakwah and Communication, 2022)
The Al- Hidayah taklim assembly activities in Simokerto district are held every Thursday afternoon from 15.00 Wib to 16.00 Wib. Consisting of congregations, most are elderly and are fostered by non-PNS Islamic religious instructors in the Simokerto district. The problem in this study is how are the characteristic of the elderly congregation and the model of the dakwah approach used by non-PNS Islamic religious instructors in conducting dakwah to the elderly assemblies. The method used in this study uses qualitative methods: data collection techniques, namely, observation, interview, and documentation. Meanwhile, in data processing, there are several ways: data reduction, selecting data, data analysis, data presentation, and drawing conclusions. The dakwah approach model used by non-PNS Islamic religious instructors in Simokerto District for the elderly congregation in the Al-Hidayah assembly uses a social approach model (bi al hal), an education approach model, a cultural education model, a personal approach model (kardiya) and a personal approach model (kardiya), group ja,' yah.